The Abrupt Transition to Distance Social Work Teaching: Lessons Learned in the Age of COVID-19. Issue 5 (20th October 2021) - Shklarski, Liat; Ray, Kathleen
ABSTRACT: Evidence of the impact of COVID-19 on higher education, specifically on social work education, is gradually emerging. While the empirical literature points to the effectiveness of delivering course content virtually, research on the impact of the abrupt, forced transition from in-person to distance teaching during the COVID-19 pandemic is limited. This quantitative study presents findings from a survey of social work instructors about their experiences during the abrupt transition from in-person to distance teaching in the first few weeks of the COVID-19 pandemic. Findings reveal that the sudden transition to distance teaching was perceived as stressful, required technological and emotional support, and workload adaptations from their institutions. The participants also reported that their worklife balance and attitudes toward distance teaching were positively affected by the change. Findings from this study also suggest the need for comprehensive institutional support to improve distance teaching methods, to prepare social work students to face the social impact of the COVID-19 pandemic, and to demonstrate that social work instructors see the benefits of online teaching and may be interested in continuing with it in the future.